FIXEL BASED ANALYSIS: AGE AND GENDER-RELATED EFFECTS OF NORMAL HEALTHY AGING ON WHITE MATTER FIBRE - CHOY, SHAO WEI (2020)
White matter fibre bundles change dynamically over the adulthood lifespan. These changes could be driven by the changes in axonal diameter, axonal density, and myelin content. In this study, the objective is to develop a pipeline to investigate the changes in fibre bundle characteristics related to a healthy ageing study by using the latest diffusion imaging technology. Limited studies had investigated alterations in fibre bundle characteristics with age, particularly in the range spanning early to late adulthood. We expanded the analysis by applying the fixel-based analysis framework using open-source pipelines with computing acceleration to examine the microscopic and macroscopic white matter changes throughout the adult lifespan. Additional processing steps were added to process low quality clinical data. By using the single shell (b=1000s/mm2) diffusion-weighted images and high-resolution T1 from a cohort of 293 healthy volunteers (89 males/204 females) ages 21 to 86 years old, we performed fixel based analysis to analyse age-related changes in microscopic fibre density and the macroscopic morphology, fibre cross-section. Whole-brain fixel based analysis was performed using the connectivity-based fixel enhancement technique to analyse the cross-sectional changes in fibre density and fibre cross-section measurements. The tract-level analysis was also performed on 11 major fibre tracts to evaluate the changes in white matter associated with age and gender.